Rare and Locally Distrributed Helminth Species of Palaearctics: Kurilonema markovi (Nematoda, Rhabdiasidae), the Lung Parasite of the Japanese Five-lined Skink, Eumeces latiscutatus (Reptilia, Sauria, Scincidae) - Kuzmin, Y.I.; Sharpilo, V.P. (Вестник зоологии, 2002)
The nematode Kurilonema markovi Szczerbak et Sharpilo, 1969 is redescribed based on new material. The validity of the genus Kurilonema Szczerbak et Sharpilo, 1969 is confirmed and its improved diagnosis is provided. Kurilonema Szczerbak et Sharpilo, 1969 is compared with and differentiated from the closely related genus Neoentomelas Hasegawa, 1989 by the presence of 6 circumoral lips, and from Entomelas Travassos, 1930, first of all, by the absence of teeth on the bottom of buccal capsule. The affinities between Kurilonema and other genera of Rhabdiasidae are discussed.